Techlash Who Makes the Rules in the Digital Gilded Age? - Wheeler, Tom (Brookings Institution Press, 2023)
As with the industrial revolution and the Gilded Age it created, new digital technology has changed commerce and culture, creating great wealth in the process, while being essentially unsupervised. Wheeler calls for an era of public interest oversight that embraces new protections for consumers and competition and encourages continued innovation